Application of Real-Time PCR method for evaluation of measles vaccine heat stability - Shahkarami, Mohammad Kazem; Shayestehpour, Mohammad; Sancholi, Alireza; Taqavian, Mohammad; Kamali Jamil, Razieh; Esna-Ashari, Fatemeh; Shahbazi, Reza (Archives of Advances in Biosciences, 2015)
The <a href="http://www.google.com/url?sa=t&rct=j&q=&esrc=s&source=web&cd=2&cad=rja&uact=8&ved=0CCQQFjAB&url=http%3A%2F%2Fatcc.custhelp.com%2Fapp%2Fanswers%2Fdetail%2Fa_id%2F564%2F%7E%2Fplaque-forming-units-%28pfu%29&ei=bO1LVI2gPM3B7Abu0YDgCA&usg=AFQjCNFarq7ctjUupieVzUk2CalBKdN65A&bvm=bv.77880786,d.ZGU">Plaque Forming Unit(PFU) and <a href="http://www.google.com/url?sa=t&rct=j&q=&esrc=s&source=web&cd=5&cad=rja&uact=8&ved=0CDcQFjAE&url=http%3A%2F%2Fwww.igb.fraunhofer.de%2Fen%2Fcompetences%2Fmolecular-biotechnology%2Fscreening-assay%2Ftissue-culture-infectious-dose.html&ei=r-1LVNf8EunW7QakrYGYCg&usg=AFQjCNH3RJiud4pIQNTngNuxzyOTI71EVQ&bvm=bv.77880786,d.ZGU">Tissue Culture Infectious Dose50(TCID50) methods are used for evaluation of vaccine heat stability and effect of various stabilizers on thermal stability of vaccines. The aim of present study is using Real-Time PCRtechniquefor estimation of vaccine degradation rate and thermal stability of measles vaccines. Lyophilized measles vaccines containing three various stabilizers were reconstituted with distilled water. Three vial of each vaccine incubated at25˚C for 0, 4 and 8 hours. Titer of virus in vaccines calculated by TCID50 method. Also after RNA Extraction and cDNA synthesis, the RNA copy numbers of viruses in vaccines were estimated by absolute quantitative Real-Time PCRtesting. The data were analyzedby SPSS 19 and Sigma Plot 11 software.The result of this study showed there is a significant relationshipbetween vaccine degradation rate calculated with TCID50 and Real-Time PCR method (p<0.05). ThereforeReal-Time PCR is a good complement or appropriate replacement to traditional methods.Titration methods based on cell culture are gold tests for titration of viral vaccines and estimation of heat stability but Real-Time PCR technique can also be used for this goals. This method is faster, cheaper and easier than TCID50.